Off-Label Use of Hydroxychloroquine in COVID-19: Analysis of Reports of Suspected Adverse Reactions From the Italian National Network of Pharmacovigilance - Fallani, Elettra; Cevenini, Fabio; Lazzerini, Pietro Enea; Verdini, Annalisa; Saponara, Simona (Journal of clinical pharmacology, 2022)
This study aimed to characterize adverse drug reactions (ADRs) to hydroxychloroquine in the setting of COVID-19, occurring in Italy in the period March to May 2020. The analysis of the combination therapy with azithromycin or/and lopinavir/ritonavir as well as a comparison with ADRs reported throughout 2019 was performed. ADRs collected by the Italian National Network of Pharmacovigilance were analyzed for their incidence, seriousness, outcome, coadministered drugs, and Medical Dictionary for Regulatory Activities classification. A total of 306 reports were gathered for the quarter of 2020: 54% nonserious and 46% serious, and half of the latter required either the hospitalization or its prolongation. However, most of them were either completely recovered (26%) or in the process of recovery (45%), except for 9 fatal cases. Throughout 2019, 38 reports were collected, 53% nonserious and 47% serious, but no deaths had been reported. Diarrhea, prolonged QT interval, and hypertransaminasemia were the most frequently ADRs reported in 2020, significantly higher than 2019 and specific for COVID-19 subjects treated with hydroxychloroquine. The logistic regression analyses demonstrated that the likelihood of serious ADRs, QT prolongation, and diarrhea significantly increased with hydroxychloroquine dosage. Coadministration of lopinavir/ritonavir and hydroxychloroquine showed a positive correlation with diarrhea and hypertransaminasemia and a negative relationship with the ADR seriousness. The combination therapy with azithromycin was another independent predictor of a serious ADR. Off-label use of hydroxychloroquine for COVID-19, alone or in combination regimens, was associated with increased incidence and/or seriousness of specific ADRs in patients with additional risk factors caused by the infection.